Designing and evaluating a specific teaching intervention on chemical changes based on the notion of argumentation in science - KABAPINAR, FİLİZ (ELSEVIER SCIENCE BV, 2010)
The present study aimed to investigate the feasibility of a teaching intervention based on argumentation in a typical Turkish classroom setting. The teaching intervention focused on the concept of chemical changes. It involves 6 arguments in total. The teaching intervention was implemented in a class of first year upper secondary school (aged 14-15) students during the time provided by normal chemistry curriculum. The findings indicated that argumentation improved students' chemistry knowledge and promoted their conceptual understanding. Findings also revealed that students who followed instruction based on argumentation significantly out-perform others who followed the constructivist teaching in terms of conceptual understanding. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Argumentation; conceptual understanding; chemical reactions; secondary science; CONCEPTUAL CHANGE; DISCOURSE; THINKING